The Impact of Foreign Investor Ownership Level on Agency Problems of Manufacturing Companies in Indonesia - Ahmad Cahyo Nugroho; Dedi Febrianto; Avia Enggar Tyasti; Christian Kuswibowo (Journal of Accounting and Investment, 2020)
Research aims: Investment plays an essential role in the business growth of a company and the economy to develop more broadly. The role makes each institution implement investment targets and takes all actions to support the realization of investment targets. This study proves that foreign investors can change the investment behavior of companies and the interaction among decisions.Design/Methodology/Approach: The study used a dynamic panel data analysis method based on the financial statements of 100 manufacturing companies listed on the Indonesia Stock Exchange (IDX).Research findings: Increasing foreign ownership does not always reduce agency problems. The analysis shows that the level of share ownership of foreign investors changed the company’s investment behavior. These results indicate that there are different agency problems in different ownership level of foreign investors.Theoretical contribution/Originality: This study provides a new perspective and empirical evidence that the relationship between agency problems and foreign share ownership is not static.Practitioner/Policy implication: This study analyzes the effect of the composition of foreign investors on the allocation of corporate funds by investigating capital asset investment and current asset investment interactions. This research contributes to the firm's ability to control its own goals.Research limitation/Implication: This research has not considered the company's risk characteristics related to the type of industry. For further research development, it is necessary to consider the company's risk characteristics to enhance the analysis.